Bionicle, Vol. 1: Rise of the Toa Nuva - Farshtey, Greg; D'anda, Carlos; Elliott, Randy (New York : Papercutz, 2000)
Six mighty heroes--the Toa--arrive on a tropical island to find a land under siege. The Great Spirit Mata Nui has been cast into an unending sleep by the evil Makuta. Now Makuta is attacking the island's Matoran villagers with vicious Rahi beasts. The Toa must combine their skills and elemental and mask powers to defeat Makuta and restore peace to the island. In the second story, The Toa return to the island named for Mata Nui to find it is being overrun by mechanical insects called Bohrok. These Bohrok have been unleashed by Makuta and are rapidly destroying trees, mountains, rivers, villages and anything else in their path. After a long, difficult battle, the Toa are able to defeat the queens of the swarms and end the Bohrok threat...for now. During the fight, the heroes are transformed into Toa Nuva, with new armor, new weapons, and new Masks of Power.
Keywords: Graphic Novels -- Science Fiction -- Comic Book